AUTOMOBILE SHOP CENTER DI SURAKARTA DENGAN PENDEKATAN ARSITEKTUR METAFORA - Eka Ari Setiawan; Agung Kumoro; Ana Hardiana (ARSITEKTURA, 2014)
Abstract: Automobile Shop Center in Surakarta with Metaphore Architecture approach is a building which planned to be a center of place where selling new car and second car, showroom, automotive service center (car service, car body repair, genuine parts, and test drive) located in Surakarta with Metaphore Architecture approach. The problem is how to formulate the concept of Automobile Shop Center as the center of place that accommodate many  activities such as new car selling  and second car selling, showroom, automotive service center (car service, car body repair, genuine parts, and test drive) located in Surakarta with applied Metaphore Architecture approach on this building form. Metaphore Architecture approach could be applied on Automobile Shop Center building form, have the main purpose to strengthen the perception and interpretation of the viewer about what is this building function and what is this building could do. Keyword: Place where selling new car and second car , Metaphore Architecture approach